Hubungan Antara Kualitas Tidur dan Tingkat Kelelahan dalam Latihan Teknik Atlet Pencak Silat Kategori Gerak di Wilayah Malang Raya - Shofiatul Ummah; Kurniati Rahayuni (Universitas Negeri Surabaya, 2026)
Background: This study was conducted to find out the importance of maintaining sleep quality in supporting the recovery and performance of pencak silat athletes in the movement category. Methods: This study was conducted with a correlational approach with purposive sampling techniques on 30 pencak silat athletes. The instruments used were the Pittsburgh Sleep Quality Index (PSQI), Fatigue Assessment Scale (FAS), Rating of Perceived Exertion (RPE). The data analysis technique used in this study was the Spearman Rho correlation test. Results: The results showed a significant relationship between sleep quality and post-exercise fatigue levels (0.022 <0.05), with a correlation value of 0.415, indicating a moderate relationship between the two variables. Further analysis revealed no significant relationship between sleep quality and post-exercise fatigue levels (0.703 >0.05), with a correlation value of -0.073, indicating a negative relationship, meaning an inverse relationship (the better the sleep quality, the lower the fatigue level, and vice versa). Conclusions: The post-exercise correlation (r=0.415) indicated a moderate relationship between the two variables, between adequate rest and athlete fatigue control during exercise. The results of this study demonstrate that the proposed hypothesis is accepted, and it can be concluded that there is a significant relationship between sleep quality and fatigue levels in the technical training of pencak silat athletes in the Greater Malang area.